Procedure of organization of the production for a company of drinks and sodas (2014)
The organization of the production constitutes a way of elevating the level of efficiency and effectiveness in the companies. The crisis economic world cup has resulted in a depression in the market of drinks. For what becomes necessary a better organization of the production in this sector to optimize the resources to use and to achieve the proposed objectives. Keeping in mind it this work intends as general objective: to design a procedure of organization of the production for this sector. As a result main of the work they are obtained: a procedure of the organization of the production focused in the client's necessities, being recognized in the organization the necessity of the integrity of all the parts of the system to achieve the effectiveness and the efficiency. This it was applied in the Company of Drinks and Sodas of Havana, Cuba with a remarkable impact in the sales.